Characterising the impact of COVID-19 environment on mental health, gender affirming services and socioeconomic loss in a global sample of transgender and non-binary people: a structural equation modelling. Issue 3 (22nd March 2021) - Restar, Arjee Javellana; Jin, Harry; Jarrett, Brooke; Adamson, Tyler; Baral, Stefan David; Howell, Sean; Beckham, S Wilson
Abstract : Background: We characterised the impact of COVID-19 on the socioeconomic conditions, access to gender affirmation services and mental health outcomes in a sample of global transgender (trans) and non-binary populations. Methods: Between 16 April 2020 and 3 August 2020, we conducted a cross-sectional survey with a global sample of trans and non-binary people (n=849) through an online social networking app. We conducted structural equational modelling procedures to determine direct, indirect and overall effects between poor mental health (ie, depression and anxiety) and latent variables across socioecological levels: social (ie, reduction in gender affirming services, socioeconomic loss impact) and environmental factors (ie, COVID-19 pandemic environment). Results: Anxiety (45.82%) and depression (50.88%) in this sample were prevalent and directly linked to COVID-19 pandemic environment. Adjusted for gender identity, age, migrant status, region, education and level of socioeconomic status, our final model showed significant positive associations between relationships of (1) COVID-19 pandemic environment and socioeconomic loss impact (β=0.62, p<0.001), (2) socioeconomic loss impact and reduction in gender affirming services (β=0.24, p<0.05) and (3) reduction in gender affirming services and poor mental health (β=0.19, p<0.05). Moreover, socioeconomic loss impact and reduction in gender affirming services were found to be partial mediators in this model. Conclusion: The study results supported the importance of bolstering access to gender affirming services and strengthening socioeconomic opportunities and programmatic support to buffer the impact of COVID-19 pandemic environment on poor mental health among trans and non-binary communities globally.